Existência e multiplicidade de solução para uma classe de equações elípticas quaselineares sobre R com perturbação - Maria Jose Alves (2008)
This paper is concerned with the existence of one positive solution ( in the homogeneous case ) and of two positive solutions ( in the nonhomogeneous case )for a class of quasilinear elliptic equations in R involving the p-Laplacian, with a non autonomous